RELATIONSHIP NETWORK CHARACTERISTICS OF SPORTS AND NON-SPORTS YOUNG ADOLESCENTS - Blatt, Péterné (Stadium - Hungarian Journal of Sport Sciences, 2021)
From school onwards, children spend more and more time with their peers without direct adult supervision. In peer groups, the emphasis is on shared interests, understanding and trust, rather than joint activities. The biological changes associated with adolescent sexual maturation also lead to changes in social relationships. The topic is particularly topical now, in the wake of the COVID-19 pandemic, when opportunities for face-to- face communication have been significantly reduced, leading in many cases to a transformation of relationships. Playing sport expands the individual’s range of experience: he or she is exposed to a new social environment, has the opportunity to form new relationships, and encounters a new set of values and norms. All this shapes their personality, their individuality and has an impact on their whole life. However, many children today do not play sport regularly, partly because of the increased mental workload and demands and the resulting lack of time. In my research, I was looking for answers to the question of how regular sporting activities affect the social relationships of young adolescents. As the data from my research show, regular sporting activity has a beneficial effect on both the extension and the intensity of children’s relational networks, especially for those playing team sports.